Human rights and the modern World - "Chopra, J. K" (New Delhi, 2010)
Human Rights and the Modern World deal with the questions posed by this topic is by no means to cover the entire field of civil liberties and civil rights under the United States Constitution. The topic itself is rather awkward to handle. I will consider primarily how and to what extent the Bill of Rigths has been "nationalized," that is to say made applicable to the states through the Fourteenth Amendment, and with what consequences to the division of powers and the relations between the national and state governments. This may seem like too narrow a topic, and it will be hard to stay strictly within these bounds; but toward the end of the article I will touch upon the broader question of state versus national protection of civil rights under federal-type constitutions..
Keywords: Human rights-International